Feasibility Analysis Seaweed (Eucheuma Cottonii) Long Line System in the Village District of Pa’jukukang Rappoa Bantaeng - -, Yuliana (Journal of Social and Development Sciences, 2017)
This study aims to calculate and analyze the feasibility of seaweed farming (Eucheuma cottonii) long line system in the village of the District Rappoa Pa’jukukang Bantaeng. Subjects were farmerâ€™s seaweed farming in the village Rappoa. With the number of respondents as many as 30 people. Data were collected by using observation, interview and questionnaire administration. The data were analyzed qualitatively and quantitatively using criteria analysis: analysis of the feasibility of operating revenue, revenue analysis cost ratio (R / C), analysis and Breakeven point (BEP). This research was conducted in the village of the District Rappoa Pa’jukukang Bantaeng selected intentionally (purposive) based on the consideration that the village Rappoa Bantaeng located in the coastal city where people do a lot of seaweed farming activities, to meet their needs. The results showed that the analysis of revenues and revenue cost ratio (R / C) can be interpreted that the cultivation of seaweed at the water village of the District Rappoa Pa’jukukang Bantaeng experiencing gains, based on the criteria of the R / C is more than 1. While based Break Event point (BEP) break-even point will be reached when the cultivation of seaweed dried seaweed produce as much as 264 kg or breakeven will be achieved at the price of selling seaweed for Rp.5.461 / kg. So that it can be interpreted that the cultivation of seaweed (Eucheuma cottonii) long line system in the village Rappoa feasible, or can be explained that the capital Rp.3.429.482 we can get the seller by 1.46 times the amount of capital. So from the results of this study can be generalized that seaweed farming (Eucheuma cottonii) with Long line system in the village of the District Rappoa Pa’jukukang Bantaeng feasible.